Ecomorfologia e dieta como ferramentas ecológicas para análises da influência das condições ambientais nas assembleias de peixes de riachos neotropicais. - Garcia, Thiago Deruza (2019)
In the current scenario, streams are subjected to several negative effects caused by the rapid expansion of urban centers. The use and occupation of the soil by humans alter the dynamics and functioning of these ecosystems, compromising their structure and modifying their ecological interactions. Thus, the objective was to evaluate if the environmental conditions resulting from human activities negatively affect the variability of ecomorphological traits of fish assemblages in urbanized and non-urbanized streams. Samplings were carried out in 10 neotropical streams (urbanized and non-urbanized), with the aid of electric fishing. A total of 22 linear morphological measures related to trunk, fins, head and mouth were used to calculate the ecomorphological indices. For quantification of alimentary contents, the volumetric method and frequency of occurrence were used, being combined in the alimentary index. Significant differences in the variability of ecomorphological features between urbanized and non-urbanized streams were observed. When evaluating the relationship between environmental variables and ecomorphological traits, we observed 16 significant correlations. The analyzed species consumed 22 types of food resources, being detritus, Trichoptera larvae, vegetable, fruits and seeds, larvae of Simuliidae and Chironomidae the most consumed items. Of these, larvae of Odonata, Coleopteraterrestre, Lepidoptera terrestre and Isoptera stood out as exclusive items in the diet of fish caught in non-urbanized environments.